IDENTIFYING THE INTELLECTUAL FRAMEWORK OF GREEN HRM: A BIBLIOMETRIC ANALYSIS - Verma, Ravish Chandra; Singh, Rajat Kumar; Kumar, Rishi Bhushan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study offers a comprehensive bibliometric analysis of the literature on Green Human Resource Management (GHRM) from 2013 to 2023. The Scopus database is used as the main source for extracting data. The study includes article titles, abstracts, keywords, authors, affiliations, publication dates, and citation counts. It utilizes descriptive statistics, trend analysis, and citation metrics to reveal important findings. The findings demonstrate a significant rise in GHRM research throughout the previous decade, with journal papers being the prevailing mode of publishing. The journal Sustainability, based in Switzerland, has the top position as the most significant publication in the subject. It is closely followed by the International Journal of Manpower and the Journal of Cleaner Production. The report further highlights prominent researchers and collaborative networks, emphasizing the significance of cooperation in advancing GHRM research. Significant developments in leadership, innovation, environmental performance, and employee behaviour are observed as key topics. This study not only documents the development of GHRM but also emphasizes important articles and proposes potential areas for further research.